Association between maternal nutritional status in pregnancy and offspring cognitive function during childhood and adolescence; a systematic review. Issue 1 (December 2016) - Veena, Sargoor; Gale, Catharine; Krishnaveni, Ghattu; Kehoe, Sarah; Srinivasan, Krishnamachari; Fall, Caroline
Abstract Background The mother is the only source of nutrition for fetal growth including brain development. Maternal nutritional status (anthropometry, macro- and micro-nutrients) before and/or during pregnancy is therefore a potential predictor of offspring cognitive function. The relationship of maternal nutrition to offspring cognitive function is unclear. This review aims to assess existing evidence linking maternal nutritional status with offspring cognitive function. Methods Exposures considered were maternal BMI, height and weight, micronutrient status (vitamins D, B12, folate and iron) and macronutrient intakes (carbohydrate, protein and fat). The outcome was any measure of cognitive function in children aged <18 years. We considered observational studies and trials with allocation groups that differed by single nutrients. We searched Medline/PubMed and the Cochrane Library databases and reference lists of retrieved literature. Two reviewers independently extracted data from relevant articles. We used methods recommended by the Centre for Reviews and Dissemination, University of York and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results Of 16, 143 articles identified, 38 met inclusion criteria. Most studies were observational, and from high-income settings. There were few randomized controlled trials. There was consistent evidence linking maternal obesity with lower cognitive function in children; low maternal BMI has been inadequately studied. Among three studies of maternal vitamin D status, two showed lower cognitive function in children of deficient mothers. One trial of folic acid supplementation showed no effects on the children's cognitive function and evidence from 13 observational studies was mixed. Among seven studies of maternal vitamin B12 status, most showed no association, though two studies in highly deficient populations suggested a possible effect. Four out of six observational studies and two trials (including one in an Iron deficient population) found no association of maternal iron status with offspring cognitive function. One trial of maternal carbohydrate/protein supplementation showed no effects on offspring cognitive function. Conclusions Current evidence that maternal nutritional status during pregnancy as defined by BMI, single micronutrient studies, or macronutrient intakes influences offspring cognitive function is inconclusive. There is a need for more trials especially in populations with high rates of maternal undernutrition. Systematic review registration Registered in PROSPEROCRD42013005702 .